LEGAL ANALYSIS OF MULTIPLE LAND CERTIFICATES: A CASE STUDY IN INDONESIA - Ikhwan, Muhammad; Widjaja, Gunawan (CV. Lafadz Jaya, 2025)
This research analyses the legal problems caused by the existence of multiple land titles in Indonesia, which reflect weaknesses in the country's land administration system. Multiple title cases not only create legal uncertainty and increase land disputes but also burden the judicial system with lengthy and complex legal processes. The economic impact is felt across sectors, with delays in property development and declining property values, affecting individuals, investors and financial institutions. The study emphasises the importance of legal reform and improvement of the land registration system with the adoption of modern technology and increased supervision. This will lead to a more transparent, accurate and reliable land administration system, reducing the potential for multiple land titles and providing better legal protection to landowners.